LINGUOCULTURAL FEATURES OF NATIONAL WORLDVIEW IN LANGUAGE (SCIENCE TIME JOURNAL, 2026)
This article investigates the relationship between language and culture from the perspective of linguoculturology. The study focuses on the role of language in reflecting the national worldview and preserving cultural values. Linguistic units such as phraseological expressions, proverbs, and culturally marked vocabulary are analyzed as carriers of cultural information. The research applies descriptive and comparative methods to identify linguocultural features embedded in language. The findings reveal that language functions not only as a means of communication but also as a repository of national identity and collective cultural experience.